1984
DOI: 10.1002/jhet.5570210559
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and reactions of 2,3‐diamino‐4(3H)‐pyrimidinones and 3‐amino‐2‐hydrazino‐4(3H)‐pyrimidinones. I

Abstract: A series of new 2,3‐diamino‐4‐pyrimidinones and 3‐amino‐2‐hydrazino‐4‐pyrimidinones were synthesized by the reactions of β‐ketoesters with amino or diaminoguanidines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…The starting 2-methyl-7-phenylpyrimido [1,2-b] [1,2,4]triazepine -4,9(3H,5H)-dione (3) was prepared by condensation of ethyl acetoacetate (1) with 2,3-diamino-6-phenylpyrimidin-4(3H)one (2). 9 Although the reaction of 1 with 2 can lead theoretically to 3 and/or its isomer the 4-methyl-7-phenylpyrimido [1,2b]triazepine-2,9(1H,3H)-dione 5, the latter structure was ruled out on the basis of the fact that condensation reactions of ethyl acetoacetate with C,N-1,2-diaminoheterocycles thus far studied have been reported to be regioselective, leading to products that result from nucleophilic attack of the N-NH 2 and the C-NH 2 groups at the keto and ester carbonyl groups, respectively, of the β-keto ester to give the corresponding fused 4-oxo-1,2,4-triazepine derivatives. [10][11][12][13] This regioselectivity was substantiated by X-ray crystallographic analysis in some cases 13 and by spectral data.…”
Section: Resultsmentioning
confidence: 99%
“…The starting 2-methyl-7-phenylpyrimido [1,2-b] [1,2,4]triazepine -4,9(3H,5H)-dione (3) was prepared by condensation of ethyl acetoacetate (1) with 2,3-diamino-6-phenylpyrimidin-4(3H)one (2). 9 Although the reaction of 1 with 2 can lead theoretically to 3 and/or its isomer the 4-methyl-7-phenylpyrimido [1,2b]triazepine-2,9(1H,3H)-dione 5, the latter structure was ruled out on the basis of the fact that condensation reactions of ethyl acetoacetate with C,N-1,2-diaminoheterocycles thus far studied have been reported to be regioselective, leading to products that result from nucleophilic attack of the N-NH 2 and the C-NH 2 groups at the keto and ester carbonyl groups, respectively, of the β-keto ester to give the corresponding fused 4-oxo-1,2,4-triazepine derivatives. [10][11][12][13] This regioselectivity was substantiated by X-ray crystallographic analysis in some cases 13 and by spectral data.…”
Section: Resultsmentioning
confidence: 99%
“…Because this procedure required an additional step (evaporation of ethanol under reduced pressure) and considering that the reported yield (41%) was not particularly high, we decided to follow the classic method, notwithstanding the existence of other reports on the alkoxide method . The method we used in this study was reported for the first time in 1886 by Behrend, and employed subsequently with satisfactory yields . The global yield of the reaction can be improved by assuring propitious conditions for enhanced recovery of the precipitate, e. g. low temperatures during filtration and washings, and additional recovery of precipitate from the first‐run filtrates by re‐precipitation with large amounts of water.…”
Section: Resultsmentioning
confidence: 99%
“…The starting 4-phenyl-1,3-dihydro-[1,2,4]triazepino[2,3- a ]quinazoline-2,7-dione 4 was prepared by condensation of 2,3-diamino-quinazolin-4-one 1 [ 25 ] with ethyl benzoylacetate 2 in acetic acid under reflux. The structure of 4 was indicated by its elemental and spectral (IR, 1 H-NMR and MS) analyses (see the experimental section).…”
Section: Resultsmentioning
confidence: 99%
“…Elemental analyses were carried out at the Microanalytical Laboratory of Cairo University, Giza, Egypt. 2,3-Diamino-quinazoline-4-one 1 was prepared as previously described [ 25 ].…”
Section: Methodsmentioning
confidence: 99%